Profiles of personal characteristics and relevant pathways in the junior-to-senior transition : a longitudinal study of Swedish athletes - Franck, A.; Stambulova, N. B.; Weibull, F. (International Journal of Sport Psychology, 2016)
In this study the specific foci were as follows: (1) to identify profiles of athletes in the junior-to-senior transition (JST) based on their personal characteristics (athletic identity, self-esteem and goal orientation) and (2) to describe the JST pathways relevant to the profiles. This quantitative longitudinal study included five measurements that were conducted approximately every six months. The following package of four instruments was used: the Athletic Identity Measurement Scale (Brewer, Van Raalte, & Linder, 1993), the Task and Ego Orientation in Sport Questionnaire (Duda, 1989), the self-esteem sub-scale from the Physical Self-Perception Profile - Revised (Lindwall, Hagger, & Asci, 2007) and the Transition Monitoring Survey (Stambulova, Franck, & Weibull, 2012). In the first measurement 100 club-based Swedish athletes (73 male and 27 female) with the mean age of 16.51 (SD = 1.32) participated. The Latent Profile Analysis resulted in three profiles of athletes. Further, several similarities and differences were found in the JST pathways between athletes representing the three profiles. Athletic identity appeared to be a key personal characteristic that influenced the dynamics of the JST adjustment. Different styles of coping strategies were also associated with different JST pathways. The JST pathways relevant to the profiles are discussed based on the theoretical framework and previous research.